2017
DOI: 10.1016/j.micpath.2017.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Identification and initial characterisation of a protein involved in Campylobacter jejuni cell shape

Abstract: Campylobacter jejuni is the leading cause of bacterial food borne illness. While helical cell shape is considered important for C. jejuni pathogenesis, this bacterium is capable of adopting other morphologies. To better understand how helical-shaped C. jejuni maintain their shape and thus any associated colonisation, pathogenicity or other advantage, it is first important to identify the genes and proteins involved. So far, two peptidoglycan modifying enzymes Pgp1 and Pgp2 have been shown to be required for C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…In addition, changes in cell shape and an alteration in peptidoglycan structure resulting from pgp1 and pgp2 mutations also altered levels of activation of human host cell receptors in response to infection [80, 93], indicating a possible advantage of the change in cell shape. An isolate showing a similar elongated helical morphology to that observed in our study, arising from mutation in a different gene ( Cj1564 ), showed decreased ability to migrate through agar and decreased ability to adhere to and invade Caco-2 cells, however, it showed no impairment in chick colonization [83]. These findings collectively indicate that cell shape variation could be adaptive in the systemic niche, though ability to colonize a new host could potentially be compromised.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, changes in cell shape and an alteration in peptidoglycan structure resulting from pgp1 and pgp2 mutations also altered levels of activation of human host cell receptors in response to infection [80, 93], indicating a possible advantage of the change in cell shape. An isolate showing a similar elongated helical morphology to that observed in our study, arising from mutation in a different gene ( Cj1564 ), showed decreased ability to migrate through agar and decreased ability to adhere to and invade Caco-2 cells, however, it showed no impairment in chick colonization [83]. These findings collectively indicate that cell shape variation could be adaptive in the systemic niche, though ability to colonize a new host could potentially be compromised.…”
Section: Discussionsupporting
confidence: 69%
“…Phase variation in pgp1 was observed in one gastrointestinal ST50 isolate, but pgp1 also carried unique nonsynonymous substitutions in H1604 and H1664 and a truncation in H1664. Similar to pgp1 , pgp2 is also involved in mediating cell morphology and deletion has been shown to cause a switch to rod-shaped morphology and defects in motility and biofilm formation, as well as impairment in a chick colonization model [ 83 ]. Because we identified mutations in both mreB and pgp1 , we examined the sequences for this gene as well.…”
Section: Resultsmentioning
confidence: 99%
“…adverse conditions of the gastrointestinal tract, to finally colonise the jejunum and ileum of the host [4,5]. Adhesion to epithelial cells of the animal gastrointestinal tract is thus the first important step for successful colonisation.…”
mentioning
confidence: 99%
“…However, to establish an infection, Campylobacter spp. first adhere to and persist in the mucus layer that covers the intestinal epithelium, and thus survive the adverse conditions of the gastrointestinal tract, to finally colonise the jejunum and ileum of the host [4,5]. Adhesion to epithelial cells of the animal gastrointestinal tract is thus the first and important step for successful colonisation.…”
Section: Introductionmentioning
confidence: 99%